ANALISIS TINGKAT PENDAPATAN USAHA KERAJINAN KAIN TENUN GEDOGAN DI DESA PRINGGASELA KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - Halizah, Halizah; Mimi Cahayani (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2022)
The title of this research is the analysis of the income level of the gedogan woven craft business in Pringgasela Village, Pringgasela District, East Lombok Regency. The purpose of this study is to find out how the income level of the gedogan Pringgasela woven fabric business is, to find out what are the obstacles to the gedogan Pringgasela woven fabric craftsmanship. The type of research used in this study is descriptive research with a quantitative approach, Data Analysis Techniques used to analyze the formulation of the first problem regarding income analysis of gedogan pringgasela weaving by inputting all the data that has been obtained regarding product costs in the table. Using cost, revenue, and revenue analysis. Based on the results of the research and discussion above, it can be concluded that the level of income (net income) of the gedogan woven fabric business, Pringgasela village, Pringgasela district, East Lombok regency, total variable costs incurred in 1 (one) period of gedogan woven fabric entrepreneurs are calculated in form of gross income with the amount of RP. 272,500,000 with an average of Rp. 27,250,000. Then the revenue obtained by entrepreneurs of gedogan woven fabrics in Pringgasela Village, Pringgasela District, East Lombok Regency. With an average net income of Rp.89,200,000, with an average income value of Rp. 8,920,000.